1996
DOI: 10.1007/bf01247372
|View full text |Cite
|
Sign up to set email alerts
|

Differential kinetics of [123I]?-CIT binding to dopamine and serotonin transporters

Abstract: Iodine-123-labelled 3beta-(4-iodophenyl)tropane-2beta-carboxylic acid ([123I]beta-CIT) labels both the dopamine transporter (DAT) and the serotonin transporter (5-HTT) and this ligand is able to clarify pathological changes in both dopaminergic and serotonergic systems. However, the differential kinetics of beta-CIT binding to DAT and 5-HTT has not been clarified fully. In this study we examined time-activity curves of [123I]beta-CIT in individual regions in the rat brain. Using cerebellum as the reference reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Another possibility is that the lower observed BP derives from the model used to estimate kinetic parameters. However, we calculated the estimated kinetics of [ 123 I]␤-CIT and [ 123 I]nor-␤-CIT with the model described by Fujita et al (1996). By using this model, we found similar kinetics of [ 123 I]␤-CIT binding in rat brain as reported by Fujita, which give support to the observed kinetic characteristics of [ 123 I]nor-␤-CIT.…”
Section: Discussionsupporting
confidence: 85%
“…Another possibility is that the lower observed BP derives from the model used to estimate kinetic parameters. However, we calculated the estimated kinetics of [ 123 I]␤-CIT and [ 123 I]nor-␤-CIT with the model described by Fujita et al (1996). By using this model, we found similar kinetics of [ 123 I]␤-CIT binding in rat brain as reported by Fujita, which give support to the observed kinetic characteristics of [ 123 I]nor-␤-CIT.…”
Section: Discussionsupporting
confidence: 85%
“…21,23 In the hypothalamic/midbrain area, including raphe nuclei, ventral tegmental area, substantia nigra and the colliculi containing mainly serotonin transporters, [ 123 I]␤-CIT uptake reaches its highest value at 1-2 h after the injection. Thalamic activity (serotonin transporters) peaks at 4 h after the injection 24,25 correspondingly. Since previous studies have not revealed significant changes in blood flow either in the hypothalamus/midbrain area or in the thalamus in depressive states 52 ]␤-CIT in prefrontal cortex is low and rather within PET than SPET resolution.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…22 This ratio can be used as an estimate of binding potential since the state of equilibrium has been documented to exist in the striatal and occipital areas at 24 h after the injection. Based on the findings of serotonin transporter binding kinetics, 21,[23][24][25][26] the following ratios at 1, 4 and 24 h after the injection were used for semiquantification of the serotonin transporters: HMB/OWM, Th/OWM and PF/OWM, the optimal imaging time in hypothalamic/midbrain area being 1 h, and in thalamus 4 h after the injection. 25,26 …”
Section: Spet Imagingmentioning
confidence: 99%
“…In the present study, we used the radioactivity in the cerebellum as the input function for the kinetic analysis or the nonspecific binding of [ 123 I]␤-CIT in brain, as previously reported (Fujita et al, 1996(Fujita et al, , 1997. No significant changes in radioactivity in the cerebellum were observed in the MK-801 pretreated rats (Fig.…”
Section: Discussionmentioning
confidence: 90%